Průmyslová hala - Čerbák, Jakub (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Cílem bakalářské práce je návrh a posouzení ocelové nosné kontrukce průmyslové haly. Příčná vazba je tvořena rámem s náběhy o rozpětí 30 m a půdorysné délce 72 m. Výška ve středu vazby je 10,3 m a osová vzdálenost těchto vazeb je 6 m. Použítým materiálem je ocel S355. Součástí je posouzení vybraných nosných prvků, detailů a jejich výkresová dokumentace.

The aim of the bachelor thesis was the design and assessment of the steel supporting structure of manufacturing hall. The main frame is formed by a frame with a span of 30 m and a plan length of 72 m. The height in the centre of the main frame is 10,3 m and the axial distance of these frames is 6 m. The used material is steel S 355. Thesis includes the assessment of selected load-bearing elements, details and their drawing documentation.
Industrial hall
Keywords: Ocelová kontrukce; průmyslová hala; rámová konstrukce; příčná vazba; Steel structure; manufacturing hall; frame; semi-rigid joints